Amphotericin B- and Levofloxacin-Loaded Chitosan Films for Potential Use in Antimicrobial Wound Dressings: Analytical Method Development and Its Application - Ke Peng; Mingshan Li; Achmad Himawan; Juan Domínguez-Robles; Lalitkumar K. Vora; Ross Duncan; Xianbing Dai; Chunyang Zhang; Li Zhao; Luchi Li; Eneko Larrañeta; Ryan F. Donnelly (MDPI AG, 2022)
Levofloxacin (LVX) and amphotericin B (AMB) have been widely used to treat bacterial and fungal infections in the clinic. Herein, we report, for the first time, chitosan films loaded with AMB and LVX as wound dressings to combat antimicrobial infections. Additionally, we developed and validated a high-performance liquid chromatography (HPLC) method coupled with a UV detector to simultaneously quantify both AMB and LVX. The method is easy, precise, accurate and linear for both drugs at a concentration range of 0.7-5 µg/mL. The validated method was used to analyse the drug release, ex vivo deposition and permeation from the chitosan films. LVX was released completely from the chitosan film after a week, while approximately 60% of the AMB was released. Ex vivo deposition study revealed that, after 24-hour application, 20.96 ± 13.54 µg of LVX and approximately 0.35 ± 0.04 µg of AMB was deposited in porcine skin. Approximately 0.58 ± 0.16 µg of LVX permeated through the skin. AMB was undetectable in the receptor compartment due to its poor solubility and permeability. Furthermore, chitosan films loaded with AMB and LVX were found to be able to inhibit the growth of both Candida albicans and Staphylococcus aureus, indicating their potential for antimicrobial applications.